2011
DOI: 10.1111/j.1360-0443.2011.03515.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of needle and syringe provision and opiate substitution therapy on the incidence of hepatitis C virus in injecting drug users: pooling of UK evidence

Abstract: There is good evidence that uptake of opiate substitution therapy and high coverage of needle and syringe programmes can substantially reduce the risk of hepatitis C virus transmission among injecting drug users. Research is now required on whether the scaling-up of intervention exposure can reduce and limit hepatitis C virus prevalence in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
290
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 280 publications
(303 citation statements)
references
References 39 publications
(61 reference statements)
7
290
2
1
Order By: Relevance
“…obtaining ≥ 1 sterile syringes per injection) or OST can each reduce HCV infection risk by 50%; and NSPs and OST in combination can reduce HCV infection risk by 80%. 20 However, owing to a small number of incident HCV infection cases (n = 40), the efficacy estimate for 100% coverage of NSPs was weak (95% CI 0.22 to 1.12) and there was insufficient power to evaluate whether or not a dose-response relationship exists. This project will provide a more robust understanding of the likely impact of existing coverage levels of NSPs and changes in the extent of provision.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…obtaining ≥ 1 sterile syringes per injection) or OST can each reduce HCV infection risk by 50%; and NSPs and OST in combination can reduce HCV infection risk by 80%. 20 However, owing to a small number of incident HCV infection cases (n = 40), the efficacy estimate for 100% coverage of NSPs was weak (95% CI 0.22 to 1.12) and there was insufficient power to evaluate whether or not a dose-response relationship exists. This project will provide a more robust understanding of the likely impact of existing coverage levels of NSPs and changes in the extent of provision.…”
Section: Discussionmentioning
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk Needle and syringe programmes versus lower or no needle and syringe programmes coverage A total of 15 studies reported measures of NSP exposure and HCV infection incidence, 14,20,[41][42][43][44]47,48,50,54,58 including five unpublished estimates. [33][34][35]59,60 Only five studies published adjusted estimates, 33,42,44,47,48 restricting the sensitivity analysis that could be conducted.…”
Section: Effectiveness Of Needle/syringe Programmes and Opioid Substimentioning
confidence: 99%
See 3 more Smart Citations